Pengabdian Internasional Dosen dan Mahasiswa UIN Ar-Raniry di Madrasah Tahfiz Taufiqillah Kedah, Malaysia - Mawardi, Mawardi; Mujia, Muji; Mansor, Mohammad Irhamuddin Bin; Zuniar, Zuniar; Fata, Azimul; Gawa, Muhammad Rafliansyah; Zikran, Muhammad; Yunos, Abdul Afif Bin; Andika, Aris; Raihan, Muhammad; Purba, Fahri Andra; Faiz, Muhammad; Karim, Muhammad Danish Bin Abdul; Munadia, Farah; Amelia, Ghina; Husna, Sarwatul; Pramita, Arni (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2024)
Madrasah Tahfiz Taufiqillah Kedah Malaysia is one of the Malaysian movement schools under the organization of Hal Ehwal Sekolah Agama Kedah (HESA). This madrasah was founded by Auzaid bin Ismail. On July 3-19, 2024, students and lecturers of the Ushuluddin faculty of UIN Ar-Raniry carried out international service at the madrasah. Some of the activities carried out include religious, educational, environmental, sports, and economic activities. The purpose of this international service activity is to broaden students' understanding and skills in actualizing knowledge at the international level. The method used in writing this article is to use qualitative descriptive with a participatory action research (PAR) approach. The results of this international service activity are that UIN Ar-Raniry students have succeeded in implementing community service programs that are able to motivate students at Madrasah Tahfiz Taufiqillah Kedah to present additional programs in carrying out educational education. In addition, other results are in the form of output, impact on student experience, and cooperation. This international service activity can be sustainable and create academic cooperation in two or more countries..